Recurrence risk stratification based on Epstein–Barr virus DNA to identify enlarged retropharyngeal lymph nodes of nasopharyngeal carcinoma: A model-histopathologic correlation study - Mao, Minjie; Wang, Xueping; Seeruttun, Sharvesh Raj; Chi, Peidong; Huang, Kewei; Liu, Wen; Tan, Wencheng (Frontiers in Medicine, 2022)
Background: Accurate assessment of the nature of enlarged retropharyngeal lymph nodes (RLN) of nasopharyngeal carcinoma (NPC) patients after radiotherapy is related to selecting appropriate treatments and avoiding unnecessary therapy. This study aimed to develop a non-invasive and effective model for predicting the recurrence of RLN (RRLN) in NPC. Methods: The data of post-radiotherapy NPC patients (N=76) with abnormal enlargement of RLN who underwent endonasopharyngeal ultrasound-guided fine-needle aspirations (EPUS-FNA) were examined. They were randomly divided into a discovery (n=53) and validation (n=23) cohort. Univariate logistic regression was used to assess the association between variables (magnetic resonance imaging characteristics, EBV DNA) and RRLN. Multiple logistic regression was used to construct a prediction model. The accuracy of the model was assessed by discrimination and calibration, and decision curves were used to assess the clinical reliability of the model for the identification of high risk RLNs for possible recurrence. Results: Abnormal enhancement, minimum axis diameter (MAD) and EBV-DNA were identified as independent risk factors for RRLN and could stratify NPC patients into three risk groups. The probability of RRLN in the low-, medium- and high-risk groups were 37.5%, 82.4%, and 100%, respectively. The AUC of the final predictive model was 0.882 (95% CI:0.782-0.982) in the discovery cohort and 0.926 (95% CI,0.827–1.000) in the validation cohort, demonstrating good clinical accuracy for predicting the RRLN of NPC patients. The favorable performance of the model was confirmed by the calibration plot and decision curve analysis. Conclusions: The nomogram model constructed in the study could be reliable in predicting the risk of RRLN after radiotherapy for NPC patients.